INTEGRAL HENSTOCK-STIELTJES FUNGSI BERNILAI VEKTOR - Hanung, Umi Mahnuna; Indrati, Ch. Rini (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2012)
This paper discusses about the generalization of the Henstock-Stieltjes integral for vector-valued functions which are defined on a closed interval [a,b]⊂R. The generalization has been done up to the existance of this integral. Key words: Henstock-Stieltjes integral, vector-valued function and bounded function.